IMPLEMENTASI MODEL THINK PAIR SHARE DALAM PEMBELAJARAN MENANGKAP MAKNA TEKS TANGGAPAN KRITIS SISWA KELAS IX SMPN 1 KARANGPLOSO - Dalismi Dalismi (Center of Language and Cultural Studies, 2016)
This study aims to improve motivation and learning outcomes capture the meaning of the text critical response class IX students of SMPN 1 Karangploso using learning model Think Pair Share (TPS). This type of research using the design of classroom action research with two cycles. Based on the results of learning in the second cycle there is an increase in the persistence indicator by 78%; seriousness of 76%; the attractiveness of the material 76%; independence 84%; cooperation 80%; the persistence of 82%, while the average score of exercises that 81.29% of students answered. From the data obtained by observation and questionnaires can be concluded that the implementation does learning model Think Pair Share (TPS) can improve motivation and learning outcomes capture the meaning of the text critical response class IX students of SMPN I Karangploso the academic year 2015/2016.